2017
DOI: 10.1123/japa.2015-0271
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Training With Three-Dimensional Video Games Improves Postural Balance and Lower Extremity Strength in Community-Dwelling Older Adults

Abstract: Avatar-based three-dimensional technology is a new approach to improve physical function in older adults. The aim of this study was to use three-dimensional video gaming technology in virtual reality training to improve postural balance and lower extremity strength in a population of community-dwelling older adults. The experimental group participated in the virtual reality training program for 60 min, twice a week, for 6 weeks. Both experimental and control groups were given three times for falls prevention e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 32 publications
1
78
0
1
Order By: Relevance
“…There are few studies on lower extremity muscle strengthening using virtual reality training; however, one study showed that such training in a home care setting resulted in increased lower extremity muscle strength in incomplete spinal cord injury patients [26]. Another recent report demonstrated that virtual reality training increased lower extremity muscle strength in a local community of the elderly [27]. These results support the concept that virtual reality training has a positive effect on lower extremity muscle strength.…”
Section: Discussionmentioning
confidence: 69%
“…There are few studies on lower extremity muscle strengthening using virtual reality training; however, one study showed that such training in a home care setting resulted in increased lower extremity muscle strength in incomplete spinal cord injury patients [26]. Another recent report demonstrated that virtual reality training increased lower extremity muscle strength in a local community of the elderly [27]. These results support the concept that virtual reality training has a positive effect on lower extremity muscle strength.…”
Section: Discussionmentioning
confidence: 69%
“…Three studies [ 45 , 47 , 55 ] with more than 2 groups of participants (see the above paragraph) compounded this comparison with the results of a control group that did not receive any physical intervention. Two studies [ 46 , 51 ] did not specify whether the control group performed any exercises during the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that VR-induced neuroplasticity promotes motor relearning, and this technology has been widely used in neurological rehabilitation [8]. In VR training, as the body's center of gravity moves beyond the base of support, proprioceptive sensations at the joints increase; therefore, participants are trained to adjust the balance perturbations [9]. Unlike the conventional training, the difficulty levels can be graded and fine-tuned by manipulating the angulation and speed of the stimulus.…”
Section: Introductionmentioning
confidence: 99%